First demonstration of robust tri-gate β-Ga2O3 nano-membrane field-effect transistors. (24th December 2021) - Bae, Hagyoul; Park, Tae Joon; Noh, Jinhyun; Chung, Wonil; Si, Mengwei; Ramanathan, Shriram; Ye, Peide D
Abstract: Nano-membrane tri-gate β -gallium oxide ( β -Ga2 O3 ) field-effect transistors (FETs) on SiO2 /Si substrate fabricated via exfoliation have been demonstrated for the first time. By employing electron beam lithography, the minimum-sized features can be defined with the footprint channel width of 50 nm. For high-quality interface between β -Ga2 O3 and gate dielectric, atomic layer-deposited 15 nm thick aluminum oxide (Al2 O3 ) was utilized with tri-methyl-aluminum (TMA) self-cleaning surface treatment. The fabricated devices demonstrate extremely low subthreshold slope ( SS ) of 61 mV dec −1, high drain current ( I DS ) ON/OFF ratio of 1.5 × 10 9, and negligible transfer characteristic hysteresis. We also experimentally demonstrated robustness of these devices with current–voltage ( I – V ) characteristics measured at temperatures up to 400 °C.